DINAMIKA HABITUS DIGITAL DAN KONTESTASI MODAL SIMBOLIK: ANALISIS BUDAYA FLEXING PADA GENERASI Z DALAM LANSKAP SOSIAL INDONESIA - Nafisah Nailal Husna; Syamsul Bakhri (Yayasan Literasi Sains Indonesia, 2025)
The development of social media has given rise to a culture of flexing as a social practice that is increasingly strengthening among Generation Z. Flexing not only represents a lifestyle flaunting behavior, but also functions as a symbolic strategy to gain social recognition in the digital arena. This study aims to analyze the culture of flexing on social media as a social practice using Pierre Bourdieu's theoretical framework, specifically the concepts of habitus, arena, and symbolic capital. The research method used is a literature study by reviewing relevant national and international journal articles published in the period 2020–2025. The results of the study indicate that social media acts as an arena for social status competition, where the digital habitus of Generation Z forms a disposition that normalizes flaunting behavior as something normal. Economic capital is converted into cultural capital through the visual aesthetics of content, which is then transformed into symbolic capital in the form of prestige, reputation, and social legitimacy based on digital engagement. The practice of flexing has dual implications, namely it can increase self-confidence and motivation, but also trigger social pressure, excessive social comparison, and status anxiety. This research contributes to the development of a theoretical understanding of digital symbolic capital and provides a conceptual foundation for strengthening critical media literacy among Generation Z.